REMOVAL OF LEAD BY WATER HYACINTH (EICHHORNIA-CRASSIPES) - AKCIN, G; SALTABAS, O; AFSAR, H (MARCEL DEKKER INC, 1994)
Various factor effect on removal of lead (II) by the water hyacinth (Eichhornia crassipes) were investigated. The plants were exposed to lead concentration ranging from 1 to 128 ppm. As the initial lead concentration increased, lead uptake was decreased. The uptake of lead was little effected by pH in the range of 4-8 but the effect of pH increased outside of this range. When the solution volume per plant was increased the total amount of lead uptake also increased. The effect of various concentration of EDTA on the lead uptake was examined. It was observed that removal of lead was decreased by increasing the concentration of EDTA. Stirring the solution increased removal of lead.
Keywords: LEAD; WATER HYACINTH; WATER PURIFICATION; Engineering; Environmental Sciences & Ecology